Wincenty Skrzetuski o wzajemnych relacjach stanów sejmujących w Rzeczypospolitej szlacheckiej (wybrane zagadnienia) - Organiściak, Wojciech (Studia Iuridica Toruniensia, 2012)
<!--[if gte mso 9]> <![endif]--> Wincenty Skrzetuski’s political views place him among the followers of the designers of the reform of the 18th century Republic of Poland. In his work on The Political Right of the Polish Nation, Skrzetuski described the principles according to which the Polish Parliament (Sejm) of those times functioned. Polish piarist made interesting historical digressions which showed some of the weak points of the solutions functioning in the parliamentary practice of the First Republic of Poland. Skrzetuski, discussing a procedure of parliamentary sessions, ammended in the period of Stanisław August Poniatowski, did not always clearly emphasise the solutions aiming at simplifi cation and acceleration of the course of the parliamentary sessions. It needs to be emphasized that describing the problem of parliamentary clearances, he referred to disastrous parliamentary practices and was in line with some drafters of the reforms in the gentry Republic of Poland which demanded radical changes in the clearance procedure or even in its total abolishment. Skrzetuski pointed to the fact that the senat is one of the three governing organs, the most important tasks of which is to serve and advice the king, as well as support him in performing some of public duties, including justice administration, being in charge of state unity as well as laws and citizenship freedom and mediating between a monarch and free gentry nation. Skrzetuski was among those who were fi rst to advocate the necessity of building a strong modern state. In his work on Speeches on major political matters he often warned that delaying reforms, such as introduction of the succession to the throne or maintaining the liberum veto principle, would lead to a decline and ultimate fall of the Republic. <!--[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->